The Activity of Ethanolic Extract of Cyclea barbata Miers as Inhibitor of Bacterial Biofilm Formation of Salmonella typhi - Dimes Atika Permanasari; Elly Nurus Sakinah; Ali Santosa (Faculty of Medicine, University of Jember, 2016)
Biofilm is a matrix consist of extracelullar polysaccharides from the replication of microbial cells that are irreversibly attached on the cell surface. Biofilm in bacteria S.typhi strain DT104 contains food substance for protection. Biofilm can be attached to the clutery, causing food contaminaton. Cyclea barbata Miers is a plant has flavonoid that can inhibited bacteria biofilm formation. Flavonoid is phenolic compounds that has function as antibacterial by forming complex compounds disturbing the integrity of cell membranes and inhibiting biofilm. This study aims to determine the activity of the Cyclea barbata Miers as inhibitor of S.typhi DT 104 biofilm formation. This study used Quasy Experimental design with completely randomized design This study used 28 samples consist of 5 doses groups (0.29 mg/ ml, 0.33 mg / ml, 0.40 mg / ml, 0.50 mg / ml, 0.67 mg / ml), positive group (a bacterial suspension with H2O2) and negative group (a bacterial suspension with H2O) The result showed that the increasing doseof extract will decrease the biofilm formation revealed by decreasing of Optical Density and showed One Way Anova test resulted p = 0.004. In conclusion, the ethanolic extract of Cyclea barbata Miers was able to inhibit S.typhi DT 104 biofilm formation and there was a correlation between the concentration of ethanoic extract of Cyclea barbata Miers and inhibition of S.typhi biofilm formation. Key words: biofilm, Cyclea barbata Miers, S.typhi